Tea Polyphenols Regulate Key Mediators on Inflammatory Cardiovascular Diseases - Jun-ichi Suzuki; Mitsuaki Isobe; Ryuichi Morishita; Ryozo Nagai (Mediators of Inflammation)
Tea polyphenols known as catechins are key components with many biological functions, including anti-inflammatory, antioxidative, and anticarcinogenic effects. These effects are induced by the suppression of several inflammatory factors including nuclear factor-kappa B (NF-𝜅B). While these characteristics of catechins have been well documented, actions of catechins as mediators on inflammation-related cardiovascular diseases have not yet been well investigated. In this article, we reviewed recent papers to reveal the anti-inflammatory effects of catechins in cardiovascular diseases. In our laboratory, we performed oral administration of catechins into murine and rat models of cardiac transplantation, myocarditis, myocardial ischemia, and atherosclerosis to reveal the effects of catechins on the inflammation-induced ventricular and arterial remodeling. From our results, catechins are potent agents for the treatment and prevention of inflammation-related cardiovascular diseases because they are critically involved in the suppression of proinflammatory signaling pathways.